Leksēmas ēna un pakrēslis latviešu izloksnēs - Stafecka, Anna (Baltistica, 1997)
LEXEMES ēna AND pakrēslis IN LATVIAN DIALECTS The article deals with the analysis of the nomination of shadow in Latvian dialects. Standard Latvian ēna has two main meanings: „shadow of a tree” and „shadow of a living being”. The second meaning is more widespread in dialects than the first one and is connected semantically with dialectal ēns, ēna „ghost”. Some more archaic nominations of the shadow of a living being as sejs and susētuvis have been preserved in High Latvian. Lexeme pakrēslis in Standard Latvian has a meaning „shadow of the tree”, nevertheless in dialects it has also the meaning „shadow of a living being”. The examined dialectal material shows some archaic nominations of shadow of a living being while the change of meanings is observed in Standard Latvian.